Pendidikan Yoga Asana Sebagai Aktivitas Remaja Hindu Dalam Meningkatan Kualitas Diri - Yuliandari, Ni Putu Silvia (Jayapangus Press, 2022)
The development of Yoga Asanas can become a lifestyle in today's modernization era, so that the world of education is not monotonous because it can become a cultural binder and maintain Hindu values. Educational values ​​in Yoga are very much needed in the era of modernization, because they are full of aspects of the value of physical, mental, and spiritual development (tattwa, morals, ethics, and devotional service) in improving the quality of human beings. The method used is qualitative, where data collection uses observation, interviews and literature studies. The purpose of this research; (1) to find out the process of yoga asana education as an activity for Hindu teenagers to improve their self-quality (2) the obstacles in yoga asana education as an activity for Hindu teenagers to improve their self-quality (3) an effort to increase the interest of Hindu teenagers in practicing yoga. The results showed; (1) The yoga asana education process as a Hindu youth activity in improving self-quality is divided into several stages, namely, preparation stages such as taking a bath before doing the exercise, wearing comfortable clothes, preparing the mat, choosing the right time to practice, choosing a clean and clean place. perform the movement to the maximum without forcing Then the preliminary stage which discusses calming and praying, then the core stage which discusses the essence of the process of Yoga and Surya namaskara movements. (2) Obstacles in yoga asana education as Hindu youth activities in improving self-quality barriers from physiological factors are factors related to physical physical conditions, while psychological factors are factors from mental states, fatigue factors Then (3) Efforts to improve Hindu youth's interest in practicing yoga in overcoming these obstacles is divided into three, namely, making new innovations, doing exercises with youtube tutorials, looking for a new atmosphere.